Arabidopsis ZUOTIN RELATED FACTOR1 Proteins Are Required for Proper Embryonic and Post-Embryonic Root Development - Chen, Donghong; Wang, Qiannan; Feng, Jing; Ruan, Ying; Shen, Wen-Hui (Frontiers in Plant Science, 2019)
The H2A/UBIQUITIN-binding proteins AtZRF1a/b have been reported as key regulators involved in multiple processes of Arabidopsis plant growth and development. Yet, the cellular and molecular mechanisms underlying the mutant phenotype remain largely elusive. Here we show that loss-of-function of AtZRF1a/b causes defective root elongation and deformed root apical meristem (RAM) organization in seedlings. The premature termination of the primary root in the atzrf1a;atzrf1b double mutant is associated with an advanced onset of endoreduplication and subsequent consumption of reservoir stem cells. Cytological analyses using cell type-specific markers and florescent dyes indicate that AtZRF1a/b are involved in maintenance of proper cell layer organization, determinacy of cell identity, and establishment of auxin gradient and maximum at the root tip. During embryogenesis AtZRF1a/b act dominantly in regulating the maintenance of ground tissue initial cells and production of lateral root cap. Lastly, quantitative RT-PCR analysis shows mis-expression of some key genes involved in regulating cell patterning, cell proliferation and/or hormone pathways. Our results provide important insight into AtZRF1a/b function in cell fate determinacy and in establishment and maintenance of proper stem cell reservoir during embryonic and post-embryonic root development.